New Muslim Discourses on Pluralism in the Post-Modern Age - Hasan Horkuc (International Institute of Islamic Thought, 2002)
The subject of religious pluralism can provoke a great deal of controversy. One could take the view that all religious knowledge is relative and that no one can claim absolute truth for his or her religion. Alternatively one can claim that his religion or understanding is the only truth. Religious pluralism is the theoty that all religions constitute varying conceptions of, and responses to, one ultimate, mysterious divine reality. lt concerns the legitimacy of religious diversity and the idea that no single religion has a monopoly on religious truth. Some may argue that linking religion with pluralism presents a potential threat to their religion.